Hexagonal Theory as An Evaluation Tool for Creditor Trust: A New Strategy to Prevent Fraud - Ika Anggie Wiasti; Driana Leniwati; Ahmad Juanda (Universitas Swadaya Gunung Jati, 2025)
The aim of this research is analyzes the internal credit control system by integrating the 5C7P model and the Fraud Hexagon theory to prevent fictitious lending at a branch office of a state-owned bank in East Java. Using a qualitative case study method, data were collected through in-depth interviews with 10 credit professionals, including credit proposers, supervisors, and decision-makers, with professional experience ranging from 5 to 28 years. The findings indicate that fraud is driven by six key elements: managerial pressure (stimulus), the ability to manipulate data (capability), internal-external collusion (collusion), weak verification processes (opportunity), justification of violations (rationalization), and personal or institutional ambition (ego). Although the 5C and 7P principles have been implemented, these principles are often compromised by systemic pressures and misused by those with access and authority. These findings highlight the importance of a comprehensive approach that combines administrative evaluation, behavioral analysis, and structural risk mapping to enable early fraud detection. The study recommends strengthening internal controls through the integration of AI-based technology and ethics-based governance to restore public trust. The main contribution of this research is the proposed credit evaluation model that combines administrative and psychosocial perspectives an innovative approach that remains underexplored in financial literature in Indonesia.